Proceedings. 2005 IEEE International Geoscience and Remote Sensing Symposium, 2005. IGARSS '05.
DOI: 10.1109/igarss.2005.1526756
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of change detection statistics in POLSAR images

Abstract: Abstract-Change detection in polarimetric SAR (POLSAR)images is an important topic. Three statistics are compared on both simulated and real data for their efficacy in change detection. The three statistics are the contrast ratio, the ellipticity and the Bartlett test. The relative performance for these three test statistics on the two simulations is dramatically different. The results are illustrated and explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
1
24
1
Order By: Relevance
“…The seminal work on test statistics for change detection in multilook PolSAR images was done by Conradsen et al, who proposed a generalized likelihood ratio test (LRT) for equality of two complex covariance matrices and gave the asymptotic sampling distribution for the test statistic [14]. This method, also known as the Bartlett test, was compared by Kersten et al to the alternative contrast ratio and ellipticity tests [15]. Erten et al presented a new coherent similarity measure for multitemporal multichannel SAR images by means of mutual information [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seminal work on test statistics for change detection in multilook PolSAR images was done by Conradsen et al, who proposed a generalized likelihood ratio test (LRT) for equality of two complex covariance matrices and gave the asymptotic sampling distribution for the test statistic [14]. This method, also known as the Bartlett test, was compared by Kersten et al to the alternative contrast ratio and ellipticity tests [15]. Erten et al presented a new coherent similarity measure for multitemporal multichannel SAR images by means of mutual information [16].…”
Section: Introductionmentioning
confidence: 99%
“…The location parameter µ of the FS distribution is computed analytically from (15). To match the second and third-order moments and retrieve the shape parameters ξ and ζ, we use minimum distance optimization [45] to solve…”
Section: Sampling Distribution Of the Hlt Statisticmentioning
confidence: 99%
“…T= ⋅median |w 3 − median w 3 | /c 0 (6) with being the coefficients of the diagonal subband of the Haar wavelet of the input x obtained at the first resolution scale, c 0 =0.6745 [17] [18]. The parameter introduces a smoothing factor depending on the noise level still present in the input.…”
Section: Mca With Polarimetric Data Setsmentioning
confidence: 99%
“…The approach described in [5], introduces the log-likelihood test assuming that the coherence matrices follow a complex Wishart distribution, showing a good detection performance in forested areas. The work presented in [6] introduces an inter-comparison of diverse statistical-and non-statistical-based approaches to extract changes from polarimetric data sets using simulated scenarios. The authors concluded that the assumption of the probability distribution function impacts the performance of the change detector, introducing a more difficult characterization of their detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, temporal multichannel change detection techniques are interesting considering their inherent properties which are independent of SAR imaging mode, such as the generalized variance ratio [7] and the maximum-likelihood ratio test (MLRT) [5], [8], [9]. In the case of comparing the variabilities of two multivariate populations, a natural measure is the ratio of their generalized variances: For temporal single-channel images, it is the ratio of their intensities, and for temporal multichannel images, it is the ratio of determinants of covariance matrices of polarimetric SAR (PolSAR) images.…”
mentioning
confidence: 99%